2014
DOI: 10.1597/13-110
|View full text |Cite
|
Sign up to set email alerts
|

Centralization of Services for Children Born with Orofacial Clefts in the United Kingdom: A Cross-Sectional Survey

Abstract: Objective : To examine current provision of cleft lip and/or palate services in the U.K. and compliance with recommendations made by the Clinical Standards Advisory Group (CSAG) in 1998. Design : Cross-sectional questionnaire survey. Setting : All 11 services within the U.K. providing care for children born with a cleft lip and palate. Participants : Members from each healthcare specialty in each U.K. cleft team. Interventions : Self-administered postal questionnaires enquired about the provision of cleft serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 23 publications
1
39
0
1
Order By: Relevance
“…It has been postulated that caseload may have an impact on outcome in various operative fields including pediatric surgery . As a result, centralization of the surgical and medical treatment of rare conditions in children such as orofacial clefts, brain tumors, cardiac malformations, and biliary atresia has been recommended by numerous authors. In the United Kingdom, a system of regionalized subspecialization for treating patients with EA/TEF was reported to improve outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that caseload may have an impact on outcome in various operative fields including pediatric surgery . As a result, centralization of the surgical and medical treatment of rare conditions in children such as orofacial clefts, brain tumors, cardiac malformations, and biliary atresia has been recommended by numerous authors. In the United Kingdom, a system of regionalized subspecialization for treating patients with EA/TEF was reported to improve outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out to evaluate institutions providing care for individuals with cleft lip and palate, concerning the adherence to recommendations of a competent institution, concluded that there was a centralization of services in the last decade, yet it was not possible to evaluate the efficacy in relation to better outcomes (21) . However, at national level, there is a tendency of decentralization.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, following a national review in 1998 aimed at improving outcomes (Sandy et al., ), cleft services were centralised and organised into multidisciplinary teams (MDTs) comprising surgeons, clinical nurse specialists (CNSs), speech and language therapists, dentists, orthodontists and, in most cases, clinical psychologists (Scott et al., ). Specialised cleft care is often offered over the lifespan, or at least until early adulthood.…”
Section: Introductionmentioning
confidence: 99%